Severe and frequent extreme weather events undermine economic adaptation gains of tree-species diversification - Fuchs, Jasper M.; Husmann, Kai; Schick, Jan; Albert, Matthias; Lintunen, Jussi; Paul, Carola (Springer Nature, 2024)
Forests and their provision of ecosystem services are endangered by climate change. Tree-species diversifcation has been identifed as a key adaptation strategy to balance economic risks and returns in forest stands. Yet, whether this synergy between ecology and economics persists under large-scale extreme weather events remains unanswered. Our model accounts for both, small-scale disturbances in individual stands and extreme weather events that cause spatio-temporally correlated disturbances in a large number of neighboring stands. It economically optimizes stand-type allocations in a large forest enterprise with multiple planning units. Novel components are: spatially explicit site heterogeneity and a comparison of economic diversifcation strategies under local and regionally coordinated planning by simplifed measures for α, β, and γ-diversity of stand types. α-diversity refer to the number and evenness of stand types in local planning units, β-diversity to the dissimilarity of the species composition across planning units, and γ-diversity to the number and evenness of stand types in the entire enterprise. Local planning led to stand-type diversifcation within planning units (α-diversity), while regionally coordinated planning led to diversifcation across planning units (-diversity). We observed a trend towards homogenization of stand-type composition likely selecte under economic objectives with increasing extreme weather events. No diversifcation strategy fully bufered the adverse economic consequences. This led to fatalistic decisions, i.e., selecting stand types with low investment risks but also low resistance to disturbances. The resulting forest structures indicate potential adverse consequences for other ecosystem services. We conclude that high tree species diversity may not necessarily bufer economic consequences of extreme weather events. Forest policies reducing forest owners’ investment risks are needed to establish stable forests that provide multiple ecosystem services.
Keywords: climate changes; forests; tree-species diversification; forest management strategies